Designing general biology practicum e-modules using canva to enhance science process skills of pre-service teachers - Sitepu, Dewi Rulia; Afni, Khairina (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
This study aims to produce a valid and feasible practical e-module for used during distance assisted by the Canva application, in order to develop the science process skills of students at STKIP Budidaya Binjai. This research was a R&D study using the ADDIE development model, which includes the stages of analysis, design, initial product development, implementation, and evaluation. The instruments used in this research were feasibility test questionnaires which were distributed to expert validators to validate the products that had been developed and product quality instruments which were distributed to students to determine the quality of the products being developed. After the validity test and product quality test have been measured, the product is revised according to the input provided during the trial stage and then ready to be published. The results of the feasibility test showed that this e-module received a score of 89%, categorized as very feasible. The results from the student response questionnaire indicated of 90%, categorized as very good. The results of the test indicate that the e-module for biology practicum using the canva application on students' science process skills is deemed valid and suitable for use in the science practicum learning process for students at STKIP Budidaya. The implication of this research is that using this e-module can make the learning process more interactive, there is an e-module practicum guide makes it possible to prepare students to face real experiences, too savings in equipment procurement and maintenance costs, location flexibility, learning and practice time.